1975
DOI: 10.3109/00016357509004632
|View full text |Cite
|
Sign up to set email alerts
|

Turku sugar studies XVIII: Incidence of dental caries in relation to 1-year consumption of xylitol chewing gum

Abstract: A longitudinal study was carried out in order to evaluate the caries incidence as affected by partial substitution of dietary sucrose (S) with xylitol (X), the effects of S- or X-containing chewing gums being compared during one year. The material comprised initially 102 young adults, predominantly dental and medical students, divided randomly into S- and X-groups. During the study 2 subjects were excluded, one due to lack of cooperation, the other not being allowed to enter the assigned S-group due to excessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1
9

Year Published

1988
1988
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(62 citation statements)
references
References 1 publication
2
50
1
9
Order By: Relevance
“…The present data also suggest, consistent with earlier findings (Scheinin et al, 1975), that habitual, long-term use of sugar gum may not prevent caries, despite the possible benefit of salivary stimulation by gum chewing; further studies with longer chewing times might show some increase in salivary benefits.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The present data also suggest, consistent with earlier findings (Scheinin et al, 1975), that habitual, long-term use of sugar gum may not prevent caries, despite the possible benefit of salivary stimulation by gum chewing; further studies with longer chewing times might show some increase in salivary benefits.…”
Section: Discussionsupporting
confidence: 90%
“…Studies have examined DMFS scores as a function of the effect of sorbitol gum compared with no gum (Moller and Poulsen, 1973;Glass, 1981); xylitol gum compared with no gum and with topical fluoride (Scheinin et al, 1985a,b;Kandelman et al, 1988;Isokangas et al, 1988;Kandelman and Gagnon, 1990), and xylitol gum compared with sucrose (Scheinin et al, 1975). Xylitol has been shown consistently to reduce DMFS scores, while the effect of sorbitol has been equivocal (Moller and Poulsen, 1973;Glass, 1981;Birkhed, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…In the parallel Turku chewing gum study, a negative increment of 1 surface was observed during 12 months' use of xylitol gum. However, the report of this study did not differentiate between onsets and reversals [Scheinin et al, 1975a]. So it is not clear whether the negative increment was due to an increased number of reversals, a decreased number of onsets or both.…”
Section: Remineralizationcontrasting
confidence: 69%
“…After 2 years, the sucrose group had developed 7.2 new DMFS and the xylitol group 0 [Scheinin et al, 1975b]. In a parallel 1-year chewing gum study, the group receiving a sucrose-sweetened gum developed approximately 3 new DMFS, while in the xylitol group (chewing gums sweetened with 50% xylitol and 6% sorbitol) the number of DMFS decreased by 1 DMFS [Scheinin et al, 1975a]. A collaborative WHO field study in Hungary showed a caries-preventive effect in a group of children using xylitol in gums, chocolate and other confectionery daily [Scheinin et al, 1985].…”
Section: Clinical Trials With Xylitolmentioning
confidence: 99%
“…38 A further two-year study was designed to determine whether the daily use of xylitol gum increased the efficacy of routine caries preventive measures in 11-15-yearold school children in Finland -a country with low baseline caries levels. After two years, this blind study showed a mean reduction in caries in the children chewing xylitol gum of 44% compared with the control group who did not chew any gum.…”
Section: Evidence From Clinical Trialsmentioning
confidence: 99%